An Impact of Foreign Direct Investment on Employment Generation in Nepalese Economy - Thapa, Khagendra Kumar (Adhyayan Journal, 2022)
This study aims to analyze the impact of FDI on employment generation in industrial sector of Nepal for the period of 1990-2020. For analyzing the impact of FDI, the econometric analysis likes OLS, unit root, co-integration, vector autoregressive model and Granger causality are undertaken. Results of unit root test are not stationary in level but stationary after first differenced. The result of co-integration test indicates that there is no co-integration between foreign direct investment and employment generation. This means a long-run co-integration relation between variable does not exist. The result of Granger causality test shows there is no bidirectional causality between these variables. It is seen that due to the negligible and flexible amount of FDI in Nepal, there is no long-run relationship between FDI and employment generation.